2005
DOI: 10.1590/s0034-70942005000200003
|View full text |Cite
|
Sign up to set email alerts
|

Bupivacaína racêmica a 0,5% e mistura com excesso enantiomérico de 50% (S75-R25) a 0,5% no bloqueio do plexo braquial para cirurgia ortopédica. Estudo comparativo

Abstract: RESUMOSato RTC, Porsani DF, Amaral AGV, Schulz Jr OV, Carstens AMG -Bupivacaína Racêmica a 0,5% e Mistura com Excesso Enantiomérico de 50% (S75-R25) a 0,5%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
(16 reference statements)
0
5
0
3
Order By: Relevance
“…In brachial plexus block, the enantiometric mixture (S75:R25) is a safer alternative if compared to racemic bupivacaine, due to its lower toxicity 7 . Based on a pilot study that reported reduction of postoperative pain with average analgesia of 24 hours 8 , this prospective, randomized, double-blind study was conducted to investigate the analgesia produced with bilateral pudendal blockade using levobupivacaine enantiomeric excess (S75:R25), compared to the method commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…In brachial plexus block, the enantiometric mixture (S75:R25) is a safer alternative if compared to racemic bupivacaine, due to its lower toxicity 7 . Based on a pilot study that reported reduction of postoperative pain with average analgesia of 24 hours 8 , this prospective, randomized, double-blind study was conducted to investigate the analgesia produced with bilateral pudendal blockade using levobupivacaine enantiomeric excess (S75:R25), compared to the method commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…Authors concluded suggesting that S75:R25 is a safer alternative as compared to racemic bupivacaine due to lower toxicity 16 . This study aimed at evaluating post-hemorrhoidectomy analgesia with 0.25% S75:R25 bupivacaine bilaterally injected in pudendal nerves located with the aid of electrical stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…Different animal and human studies have shown that levogyrous local anesthetics are less toxic for central nervous and cardiovascular systems as compared to racemic or dextrogyrous bupivacaine, with intrinsic ability to promote vasoconstriction and less intense motor block 14,15 . A comparison of racemic and bupivacaine with levogyrous enantiomeric excess of 50% (S75;R25) for brachial plexus block, has not shown differences in observed parameters 16 .…”
Section: Métodomentioning
confidence: 95%
See 2 more Smart Citations